Pengetahuan Masyarakat tentang Demam Berdarah Dengue di Desa Maen Kecamatan Likupang Timur Kabupaten Minahasa Utara - Sjarif, Indra Setiawan; Siagian, Iyone E.T.; Kaunang, Wulan Pingkan Julia (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Background:Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus. As known, DHF is still one of the potentially infectious disease that can cause an outbreaks / extraordinary events (KLB). The main vector of dengue is Aedes aegypti were found both in Indonesia and other subtropical countries. One of the ways to prevent this disease is to break the chain of disease transmission by mosquito nest eradication program (PSN).This study aimed to determine the knowledge of the community in the village of Maen About Dengue Fever. Methods: In this study, the method used is the survey method with a descriptive approach. Furthermore, data collected through interviews using questionnaires and measured by using Guttman scale. Numbers of samples is determined by simple random sampling with a sample of 90 households. Results:This study found that over 50% of the responden (72,2%) answered yes. Conclusions: From this study it can be concluded that the knowledge of the people in the village Maen About Dengue Hemorrhagic fever are well-knowledge. Keywords: community, dengue fever, Knowledge, Maen village.